THE EUROPEAN UNION CORPORATE SUSTAINABILITY DUE DILIGENCE DIRECTIVE: THE POST-OMNIBUS REFORM LEGAL FRAMEWORK AND A PHASED REGULATORY MODEL FOR UZBEKISTAN - Mansurov, Shohsaidkhon (Oriental Journal of History, Politics and Law, 2026)
This article presents a systematic analysis of Uzbekistan’s investment, corporate, labor, and environmental legislation from the standpoint of its compliance with due diligence standards set out in the Corporate Sustainability Due Diligence Directive (CSDDD), the UN Guiding Principles on Business and Human Rights, and the OECD Guidelines for Responsible Business Conduct. The analysis is conducted in the context of the European Union’s experience with mandatory due diligence and the amendments introduced by Omnibus I Directive (EU) 2026/470. The article also examines Uzbekistan’s reforms in implementing international labor and environmental standards, its existing capacity, and the insufficiency of the current legal framework in this area. Taking into account the key conclusions drawn from the Omnibus I package – particularly the need for phased implementation of reforms – the article proposes a four-stage model for incorporating due diligence and ESG-related standards into Uzbekistan’s national legislation. This model begins with the introduction of voluntary guidelines and mandatory sustainability reporting practices. In subsequent stages, it provides for the gradual expansion of legal obligations, culminating in the adoption of a dedicated law “On Responsible Business Conduct.”